Q-switched erbium-doped fiber laser using MoS 2 deposited side-polished D-shape fiber - Jafry, A.A.A.; Arof, Hamzah; Kasim, Nabilah; Munajat, Yusof; Apsari, Retna; Harun, Sulaiman Wadi (Old City Publishing, 2018)
A stable Q-switched erbium doped fiber laser (EDFL) emitting at 1560 nm is demonstrated by using molybdenum sulfide (MoS 2 ) material coated onto a side-polished D-shape fiber as a saturable absorber (SA). By incorporating the MoS 2 SA into the laser cavity, a stable Q-switching pulses train output centered at 1560 nm is observed at threshold pump power of 14.9 mW. As the pump power is gradually increased from 14.9 to 50.5 mW, the repetition rate of the generated pulse increases from 31.1 kHz to 75.5 kHz, while the pulse width decreases from 14.52 µs to 6.76 µs. Under a pump power of 50.5 W, an average output power of 2.47 W and a pulse energy of 32.7 nJ is obtained. This MoS 2 based SA is simple, robust and reliable and thus suitable for making a portable pulse laser source.